Comprehensive cardiac phenotyping in large animals: comparison of pressure-volume analysis and cardiac magnetic resonance imaging in pig post-myocardial infarction systolic heart failure - Raake, Philip; Barthelmes, Jens; Krautz, Birigt; Buß, Sebastian Johannes; Huditz, Regina; Schlegel, Philipp; Weber, Christophe; Haberkorn, Uwe; Katus, Hugo; Most, Patrick; Pleger, Sven Torsten (The international journal of cardiovascular imaging, 2019)
Large animal ischemic cardiomyopathy models are widely used for preclinical testing of promising novel therapeutic approaches. Pressure volume (PV) loop analysis and cardiac magnetic resonance imaging (CMRI) allow functional and morphological phenotyping. In this study we performed a comparative analysis of both methods highlighting the strength of each and their synergistic potential. Myocardial infarction (MI) was created in German farm pigs (German Landrace) by 2 h LCX occlusion (n = 11) and subsequent reperfusion. Cardiac function was assessed by PV-loops and CMRI 56 and 112 days post-MI. Two hours occlusion of the LCX led to mid-size left ventricular (LV) MI represented by high-sensitive troponin T (hsTnT) 3 days post-MI, correlating well with cardiac CMRI late enhancement. CMRI determined end-diastolic and end-systolic volumes significantly increased post-MI, while ejection fraction was reduced in infarcted animals compared to the sham group (n = 6). PV-loop derived preload-insensitive parameters of systolic and diastolic function were diminished post-MI compared to sham animals while preload-dependent parameters only deteriorated in advanced HF. PV-loop analysis significantly correlates with CMRI analysis of cardiac function in pig post-MI ischemic cardiomyopathy. PV-Loop analysis accurately quantifies LV volumetry and function in post-MI HF, and thus eccentric LV morphology. PV-loop analysis correlates well to cardiac MRI. Preload-insensitive parameters show high sensitivity to quantify HF while preload-sensitive parameters are not able to quantify early-stages of LV HF.
Gesehen am 04.11.2019